Internalisasi Nilai-Nilai Buddhisme Humanistik Pada Media Penyuluhan Agama Buddha di Fo Guang Shan - Sambhojjhanga, Virya Passaddhi; Novianti, Novianti; Sukarti, Sukarti (Gulawentah:Jurnal Studi Sosial, 2025)
This research aims to analyze the process of internalizing the values of Humanistic Buddhism in religious counseling in the Fo Guang Shan organization as well as the communication strategies used in shaping the moral consciousness of the people in the digital era. The research approach used is descriptive qualitative with literature study methods and content analysis on various sources such as texts, videos, online publications, and official documents of Fo Guang Shan. The object of the research is focused on religious counseling and educational activities under the Fo Guang Shan institution of Taiwan and its international branches, including Indonesia and Malaysia. The results of the study show that the main values of Humanistic Buddhism which include compassion, wisdom, equality, social responsibility, and self-development are internalized through the organization's four missions, namely the dissemination of teachings through culture, education, charity, and spiritual practice. The process of internalizing values takes place through the stages of recognition, understanding, acceptance, and appreciation as described by Milton Rokeach, which is then manifested in social actions and cross-cultural communication media. Fo Guang Shan's humanistic and participatory-based communication strategy has proven effective in building collective moral awareness and strengthening the role of religion as a social force in multicultural societies.